2018
DOI: 10.1111/jon.12494
|View full text |Cite
|
Sign up to set email alerts
|

Global Cerebral Atrophy Detected by Routine Imaging: Relationship with Age, Hippocampal Atrophy, and White Matter Hyperintensities

Abstract: Moderate-to-severe GCA is most likely to occur in the presence of AD or CVD and should not be solely attributed to age when evaluating clinical imaging findings in the workup of cognitive complaints. Developing optimal diagnostic and treatment strategies for cognitive decline in the setting of GCA requires an understanding of its risk factors in the aging population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…With cerebral atrophy being a typical finding in WMH (Al‐Janabi et al, ), we have shown in our present study that thinning of the RNFL and GCIP was independently associated with focal lesions in hypertensive white matter of the brain and deteriorates with the severity of the lesions. Moreover, our study also showed that both damages in the retina (thinning of the sublayers of the retina) and brain (focal lesions) may already be present in the subclinical period, during which there are no apparent clinical symptoms.…”
Section: Discussionsupporting
confidence: 72%
“…With cerebral atrophy being a typical finding in WMH (Al‐Janabi et al, ), we have shown in our present study that thinning of the RNFL and GCIP was independently associated with focal lesions in hypertensive white matter of the brain and deteriorates with the severity of the lesions. Moreover, our study also showed that both damages in the retina (thinning of the sublayers of the retina) and brain (focal lesions) may already be present in the subclinical period, during which there are no apparent clinical symptoms.…”
Section: Discussionsupporting
confidence: 72%
“…At each level, a score of 0 (absent), 1 (mild), 2 (moderate) and 3 (severe) was given. The GCA resulted from the sum of all items (from 0 to 39) [ 19 , 20 ]. White matter lesions (WML) were also analyzed on FLAIR acquisitions, with the Fazekas scale to assess white matter hyperintense lesions related to small vessels disease [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The GCA resulted from the sum of all items (from 0 to 39). [19,20] White matter lesions (WML) were also analyzed on FLAIR acquisitions, with the Fazekas scale to assess white matter hyperintense lesions related to small vessels disease. [21] This scale consisted of a score of 0 (no or single WML), 1 (multiple WML), 2 (beginning confluence of WML), or 3 (large confluent WML).…”
Section: Evaluations and Measurementsmentioning
confidence: 99%